A HOME-BASED SPORTS TRAINING IN PHYSICAL HEALTH PROMOTION FOR UNIVERSITY STUDENTS - Lifeng,Xu (2023)
ABSTRACT Introduction Physical education classes in universities have migrated to online teaching aiming to reduce the risk of infection under epidemic prevention and control normalization. However, the impact of home-based physical training on the physical health of university students is not complete because the home-based physical training program could not be adjusted in a timely manner. Objective Analyze the current situation of home-based sports training and its effect on the health of college students. Methods A questionnaire has been employed in order to analyze the current situation of home-based sports training. Sixty individuals were selected, distributed into experimental (n=30) and control group (n=30). The control group was without specific physical training while the experimental group received online monitoring from physical education teachers to perform sports training at home, three times a week, one hour a day, for a total of two months. Pre- and post-training changes were compared by in-person fitness tests. Results were contrasted via Excel and SPSS. Results Home fitness training can be accomplished in many ways, with the virtual physical education class being a primary option. The results of the influence of home-based physical training on changes in physical function of University students are considerable (P < 0.05). Conclusion Through comparison of fitness test results, home-based physical training was found to have a beneficial effect on the physical performance of college students and can be safely replicated in institutions. Level of evidence II; Therapeutic studies: investigation of treatment outcomes.